PENGARUH PENJUALAN TERHADAP RETURN ON ASSET PADA PT.KERTAS PADALARANG (SECURITY PAPER MILL) PERIODE 2020-2021 - Maryana, Diana; Rachmawati, Fitria (LAND JOURNAL, 2024)
Sales are activities carried out by sellers in selling goods and services with the dream of getting profits from these transactions and sales can be interpreted as transferring or transferring ownership rights to goods or services from the seller to the buyer. Return on Assets (ROA) is the result of return on assets which is a ratio that shows how much the contribution of assets is in creating net income. The purpose of this study was to determine the effect of sales on return on assets at PT.Kertas Padalarang (Security Paper Mill). So in this study the research method used is a quantitative method using the formulation of associative problems. The data used is primary data. While the analysis technique used is product moment correlation test, simple regression analysis, analysis of the coefficient of determination, t test. Based on the results of the analysis of sales data on return on assets, it can be concluded that there is a significant influence indicated by a significant alpha number of 0.010 <0.05.